Effectiveness of Group Counseling through Behavior Contract Techniques to Improve Student Discipline in Class X1 MAN 1 Buton - Serllan Permata Sari; Maria Ulfa; Samsaifil Samsaifil (AIQU: Journal Multidiscipliner of Science, 2023)
This research helps implement group guidance through behavior contract techniques to improve discipline which can make it easier for students to better understand their physical and social environment. The aim of this research is to determine the initial condition of discipline of class XI students at MAN 1 Buton for the 2022-2023 academic year. Based on the research results and data analysis, it can be concluded: in general, the pretest of class Post-test data in the low category consisted of 0 students, in the medium category consisted of 3 students (25%), and 9 students (75%) in the high category. The results of the Wilcoxon test analysis using the SPSS for Windows 21 computer program showed an asymp.sig (2-talied) value of 0.002<00.05, a Z value of (-2.527b) was obtained so that the hypothesis was accepted. This means that it can be concluded that providing treatment with group counseling using the Behavior Contrack technique can effectively improve student discipline.